Kontribusi Dosen Pembimbing Lapangan dalam Meningkatkan Efektifitas Program Micro Teaching Fakultas Tarbiyah dan Ilmu Keguruan Universitas Sains Al-Qur’an Wonosobo - Robingun S. El Syam; Salis Irvan Fuadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Being a teacher is a noble task because it has an important role in educating the nation and shaping the character of the new generation, because the micro teaching program is important to prepare students to become professional educators. This article aims to examine the Role of Field Supervisors in Increasing the Effectiveness of the Micro Teaching Program of the Faculty of Tarbiyah and Teacher Training, Al-Qur'an Science University, Wonosobo. The study was conducted using a qualitative descriptive method on 35 DPLs who guided 409 students in the micro teaching program. The results of the study indicate that DPLs have an important role in the effectiveness of the microteaching program by coordinating planning, implementation and reporting with the Committee, Faculty, and students, in order to ensure a significant impact for each party. In addition, student readiness and involvement appear as mediators in this relationship. These findings influence students and universities to try to enrich learning methods and strategies. Future studies can explore additional variables that further optimize the impact of multiple approaches and micro teaching on students' readiness to undergo the PPL program.